Accounting Information System Analysis of Internal Control of UPT Income Karangbinangun Lamongan Health Center - Erry Setiawan; Dwi Dewianawati; Frendy Sutikno; Eny Nuraeni (Indonesian Journal of Business Analytics, 2022)
The purpose of this study was to determine the analysis of accounting information control system of internal. Based on the measurement scale Gutman, accounting information system of the internal control values ​​obtained revenues amounting to 85.71%. This value is compared with the measurement criteria of accounting information systems with the scale Gutman including a sufficient criterion. The role of information systems in the UPT Puskesmas akuntani Karangbinangun been done adequately. Inadequate system of accounting information obtained can be identified that the management of the elements of accounting information system, the purpose of accounting information system, and the function of accounting information system has run as much as possible. So as to provide pengolalaan adequate accounting information system. Accounting information systems to work toward internal control at revenue has been done adequately. Internal control plans and methods of income is against (the elements of accounting information systems, the purpose of accounting information systems, and accounting information systems function) conducted by the internal to control income derived from activities done in a period, which will produce reliable financial statements concerning effective and efficient revenue. The results of this study, for accounting information systems at implementation should be further improved so that easier to carry out daily operations ranging from data collection, classification of data, data storage, and surveillance data to health centers can provide a more adequate control to keep the health center assets. So that the internal control income must remain in place and be effected again, so that the financial statements more valid, effective and efficient.